Metabolism-based approaches for autosomal dominant polycystic kidney disease - Bakaj, Ivona; Pocai, Alessandro (Frontiers in Molecular Biosciences, 2023)
Autosomal Dominant Polycystic Kidney Disease (ADPKD) leads to end stage kidney disease (ESKD) through the development and expansion of multiple cysts throughout the kidney parenchyma. An increase in cyclic adenosine monophosphate (cAMP) plays an important role in generating and maintaining fluid-filled cysts because cAMP activates protein kinase A (PKA) and stimulates epithelial chloride secretion through the cystic fibrosis transmembrane conductance regulator (CFTR). A vasopressin V2 receptor antagonist, Tolvaptan, was recently approved for the treatment of ADPKD patients at high risk of progression. However additional treatments are urgently needed due to the poor tolerability, the unfavorable safety profile, and the high cost of Tolvaptan. In ADPKD kidneys, alterations of multiple metabolic pathways termed metabolic reprogramming has been consistently reported to support the growth of rapidly proliferating cystic cells. Published data suggest that upregulated mTOR and c-Myc repress oxidative metabolism while enhancing glycolytic flux and lactic acid production. mTOR and c-Myc are activated by PKA/MEK/ERK signaling so it is possible that cAMPK/PKA signaling will be upstream regulators of metabolic reprogramming. Novel therapeutics opportunities targeting metabolic reprogramming may avoid or minimize the side effects that are dose limiting in the clinic and improve on the efficacy observed in human ADPKD with Tolvaptan.